ESTABLISHING POWER SPACES IN THE GOVERNMENT OF THE NATIONAL UNIVERSITY OF CORDOBA-ARGENTINA IN THE MIDDLE OF THE 20TH CENTURY - Riquelme, Norma Dolores (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2012)
Through this piece of work, it is our intention to report the way in which the students of Argentinian national universities had access to the university government and to the power that it involves- at the end of the 50s. All that was the consequence of a movement which started at the turn of the XX century and which, due to the political vicissitudes of Argentina, could not take place until the mid-twentieth century. The co-government featured the power relationships throughout the time after, even when the coups d’ etat attempted to eliminate it. Today, it is an unavoidable part of our university life, with all which that implies.